2007
DOI: 10.1038/sj.npp.1301630
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Cue-Induced Heroin-Seeking Behavior by Cannabinoid CB1 Antagonist Infusions into the Nucleus Accumbens Core and Prefrontal Cortex, but Not Basolateral Amygdala

Abstract: As with other drugs of abuse, heroin use is characterized by a high incidence of relapse following detoxification that can be triggered by exposure to conditioned stimuli previously associated with drug availability. Recent findings suggest that cannabinoid CB 1 receptors modulate the motivational properties of heroin-conditioned stimuli that induce relapse behavior. However, the neural substrates through which CB 1 receptors modulate cue-induced heroin seeking have not been elucidated. In this study, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 80 publications
(86 reference statements)
4
42
0
Order By: Relevance
“…And interestingly, the response-reinstating effect of menthol was observed only in rats that had been trained to self-administer nicotine with pre-session menthol but not in the rats that had received exactly the same nicotine self-administration training but without pre-session menthol. This finding can be explained in the frame of the above discussed occasion-setting effect of menthol and is consistent with previous studies, in which discriminative stimuli effectively reinstated extinguished drug-seeking behavior in animals that were trained to self-administer cocaine, heroin, alcohol, nicotine, and sucrose (Alvarez-Jaimes et al, 2008; Barker et al, 2014; Burbassi and Cervo, 2008; Ciccocioppo et al, 2001; Gracy et al, 2000; Kallupi et al, 2013; Katner et al, 1999; Widholm et al, 2011; Wing and Shoaib, 2008). The present results mirror our previous report that showed that caffeine influences nicotine seeking (Liu and Jernigan, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…And interestingly, the response-reinstating effect of menthol was observed only in rats that had been trained to self-administer nicotine with pre-session menthol but not in the rats that had received exactly the same nicotine self-administration training but without pre-session menthol. This finding can be explained in the frame of the above discussed occasion-setting effect of menthol and is consistent with previous studies, in which discriminative stimuli effectively reinstated extinguished drug-seeking behavior in animals that were trained to self-administer cocaine, heroin, alcohol, nicotine, and sucrose (Alvarez-Jaimes et al, 2008; Barker et al, 2014; Burbassi and Cervo, 2008; Ciccocioppo et al, 2001; Gracy et al, 2000; Kallupi et al, 2013; Katner et al, 1999; Widholm et al, 2011; Wing and Shoaib, 2008). The present results mirror our previous report that showed that caffeine influences nicotine seeking (Liu and Jernigan, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…That is, CB1 agonists administered systemically induce reinstatement of cocaine and heroin seeking, whereas CB1 antagonists block reinstatement of drug seeking (De Vries et al 2001. For heroin seeking, these effects have been localized to the core and IL-mPFC (Alvarez-Jaimes et al 2008). Hence, these effects of CB1 agents on drug seeking are in apparent opposition to their effects on fear extinction.…”
Section: Testing the Modelmentioning
confidence: 86%
“…IL neurons are Fos-activated in context-induced heroin reinstatement and inactivation of IL decreases heroin reinstatement (Bossert et al, 2011; Bossert et al, 2012). Increased zif268 is observed in IL after cue-induced reinstatement of heroin seeking (Koya et al, 2006), and inactivation of IL decreased cue and heroin prime reinstatement of heroin seeking (Rogers et al, 2008), as did infusion of CB1 antagonists in IL (Alvarez-Jaimes et al, 2008). IL inactivation also decreases cue-induced but not methamphetamine prime-induced reinstatement (Rocha and Kalivas, 2010).…”
Section: Evidence For An Imperfect Mapping Between Pl/il and Go/stopmentioning
confidence: 99%